Biosimilars: New guns for the treatment of rheumatological patients? - Daniela Marotto; Angela Ceribelli; Piercarlo Sarzi Puttini (Verduci Editore, 2019)
The advent of biological therapies in 2000s has represented a real revolution in the treatment of patients affected by rheumatic diseases, but biosimilars represent nowadays a further revolution both from an economic point of view and for the accessibility to treatment for rheumatic patients. The main scientific rheumatological societies have clearly expressed themselves on the biosimilars topic, by highlighting how they represent a great opportunity to contain costs and treat more patients, and these advantages should be accepted by rheumatologists. The use of biosimilars in different European countries varies widely; in fact, in some of them their use is mandatory (at least in naïve patients), while in other countries it is only recommended. The knowledge and consequently the acceptance of biosimilars are different among patients, and this also depends on the correct medical information on this topic. As more and more biosimilars receive regulatory approval and reach the market, it is essential for healthcare professionals to have the right knowledge about them, so that they are properly transferred to their patients. Biosimilars are not identical to the reference product, and clinicians are particularly interested in the safety and effectiveness of switching from the biooriginator to the bio-similar in experienced patients. We will develop these aspects on biosimilars in the present manuscript, for an update on current guidelines in their use in rheumatic patients.